2016
DOI: 10.1097/md.0000000000004077
|View full text |Cite
|
Sign up to set email alerts
|

Prospective clinical observational study evaluating gender-associated differences of preoperative pain intensity

Abstract: Previous studies reported conflicting results concerning different pain perceptions of men and women. Recent research found higher pain levels in men after major surgery, contrasted by women after minor procedures. This trial investigates differences in self-reported preoperative pain intensity between genders before surgery.Patients were enrolled in 2011 and 2012 presenting for preoperative evaluation at the anesthesiological assessment clinic at Charité University hospital. Out of 5102 patients completing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…Compared with the observational study of Tafelski, et al, we found no difference neither between the genders nor in dependence on age [13]. Tafelski, et al found that the difference of pain-intensity regarding genders is age-dependent.…”
Section: Discussioncontrasting
confidence: 37%
“…Compared with the observational study of Tafelski, et al, we found no difference neither between the genders nor in dependence on age [13]. Tafelski, et al found that the difference of pain-intensity regarding genders is age-dependent.…”
Section: Discussioncontrasting
confidence: 37%
“…Sex differences of experimentally induced pain have been described in the literature, reporting that women perceive physically or chemically induced pain more strongly than men [49-54, 80, 81]. These differences are not restricted to tactile perception and can be supposed for the whole body [82][83][84]. Regarding sex differences in clinical pain there are studies analysing pre-operative pain; a sex difference was found with greater pain scores for females than males [85][86][87][88][89], which was still detectable on the first post-operative day [86].…”
Section: Use Of Over-the-counter Analgesicsmentioning
confidence: 99%
“…We have not performed an anti-spike/anti-nucleocapsid antibody test to identify all previously infected participants, which may have biased the outcome of antibody level. Furthermore, potential interactions of variables were not addressable in this analysis due to limited sample size; however, sexes may differ in more dimensions such as pain-, infection-, or vaccination response [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%